PERLINDUNGAN KARYA CIPTA FOTO CITIZEN JOURNALIST YANG DIPUBLIKASIKAN DI INSTAGRAM - Marini Putri, Ni Made Dwi (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2017)
The development of the current paradigm demonstrate initiative of the citizens to share information in their possession to the public. Citizen who was only a reader, now turned into a citizen journalist, who sends the picture to the press on Instagram account on an event that attracts attention. In this research, there are two issues to be discussed namely 1) How is the protection of moral rights and economic rights over the photos produced by citizen journalist on Instagram? 2) How can the efforts of a citizen journalist to protect the copyrighted works uploaded on Instagram? This research is an empirical juridical study that examines the problem of copyright photography protection in Instagram. Moral rights protection of citizen journalist on Instagram photo is done with the mention of names of the photographer (citizen journalist) and copyright holder (press accounts on Instagram). Protection of economic rights of citizen journalism photo on Instagram as stipulated in the Act of the Republic of Indonesia Number 28 of 2014 on Copyright only applies to photographs with human objects. Efforts that can be done by a citizen journalist to protect copyrighted works uploaded on Instagram are preventive efforts, respresive efforts and pre-emtive efforts. Perkembangan paradigma di era informasi saat ini menunjukkan inisiatif dari warga untuk membagikan informasi yang dimilikinya kepada publik secara cepat dan up to date . Warga yang tadinya hanya seorang pembaca, kini cenderung menjadi citizen journalist yang cenderung berinisiatif dan aktif mengirimkan hasil fotonya kepada akun pers di Instagram mengenai suatu peristiwa yang menarik perhatian. Dalam penelitian ini terdapat dua permasalahan inti yaitu 1) Bagaimanakah perlindungan hak moral dan hak ekonomi atas foto yang dihasilkan oleh seorang citizen journalist di Instagram? 2) Bagaimanakah upaya-upaya yang dapat dilakukan seorang citizen journalist untuk melindungi karya cipta fotonya yang diunggah di Instagram? Penelitian ini merupakan penelitian yuridis empiris yang mengkaji mengenai masalah perlindungan karya cipta fotografi di Instagram. Perlindungan hak moral foto citizen journalist di Instagram dilakukan dengan penyebutan nama pencipta ( citizen journalist ) dan pemegang hak cipta (akun pers pada Instagram). Perlindungan hak ekonomi foto citizen journalist di Instagram sebagaimana yang diatur dalam Undang-undang Republik Indonesia Nomor 28 Tahun 2014 Tentang Hak Cipta hanya berlaku pada karya foto dengan objek manusia. Upaya-upaya yang dapat dilakukan seorang citizen journalist untuk melindungi karya cipta fotonya yang diunggah di Instagram adalah upaya preventif, upaya respresif serta upaya pre-emtif.